2016
DOI: 10.1021/acsmacrolett.6b00252
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Direction Control in Liquid Crystalline Photoalignable Polymeric Films by Adjusting the Free-Surface Condition

Abstract: Adjusting the free-surface condition facilely controls the in-plane and out-of-plane orientations in liquid crystalline polymer (LCP) films. Top coating with aromatic molecules onto LC polymethacrylate films with N-benzylideneaniline (NBA) or 4-methoxybiphenyl (MB) side groups (PNBAM or PMBM) and subsequent annealing generate a random planar orientation while simultaneously removing the coated aromatic molecules, whereas annealing noncoated films induces a homeotropic orientation of the mesogenic side groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…2628 have also demonstrated the control of mesogen orientation from the free surface using different types of photoreactive unit. The top skin layer can be prepared by surface segregation of a surface active photoresponsive polymer 21,22,25 or local deposition by inkjet printing 22,27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…2628 have also demonstrated the control of mesogen orientation from the free surface using different types of photoreactive unit. The top skin layer can be prepared by surface segregation of a surface active photoresponsive polymer 21,22,25 or local deposition by inkjet printing 22,27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, surface segregation has been used to modify the topmost surface, affecting the wettability and adsorption properties. The present approaches can control the internal orientation structure of the film from the free surface by a surface-segregation effect. In recent years, the effect of the free surface has been utilized to control the molecular orientation in free-standing films of various molecular systems such as liquid crystalline polymers, conductive polymers, discotic liquid crystals, and MPS structures . These approaches are anticipated to be developed as a new molecular alignment technique.…”
Section: Introductionmentioning
confidence: 99%
“…Such a surface is called the command layer 45,52,63 . Recent investigations have revealed that a photoactive command layer can be placed at the free surface in SCLCP films [41][42][43][44][45][46][47] . Similarly, the present work offers another command layer scenario where large www.nature.com/scientificreports/ molecular amplification is reflected in macroscopic surface morphing.…”
Section: Resultsmentioning
confidence: 99%
“…Related to the molecular orientation in SCLCP films, an Az-containing command layer at the free surface or inkjet-printed patterns could control the orientation of the majority of the mesogens of the base film [41][42][43][44][45] . Kawatsuki et al 46,47 also controlled of mesogen orientation from free surfaces using different types of photoreactive units.…”
mentioning
confidence: 99%